Fostering Resilience, Work-life Balance And Well Being In Promoting A Sustainable Workforce Among Women In Malaysian Public Hospitals - Yusof, Nadzrah (2023)
As employees in public hospitals institutions around the globe, women play a significant role. They have made significant advances in the public health sector and have made significant contributions to the field of medicine. Women also play an essential role in family management. Women workers particularly in public hospitals, are exposed to a variety of occupational hazards, such as long working hours, infectious diseases, excessive workload, fatigue, stress, and job insecurity, which cause them to quit their jobs or prevent them from achieving the highest level in the industry. To meet the Millennium Goals and Sustainable Development, which emphasise the importance of empowering women, it is important to understand and appreciate the contribution of women to the public health sector and to develop a sustainable workforce in health. This study seeks to examine the significance of nurturing resilience, work life balance, and wellbeing in fostering a sustainable health workforce among women in Malaysian public hospitals. This paper's theory is founded on Maslow's hierarchy of requirements, the job demands-resources model, the job demand-control model, and the spillover theory. In previous research and practise, the theoretical framework is not well linked to practise, so this study examines the combination of these theories in the context of the study of women working in public hospitals in Malaysia. Based on the results, demographic factors are positively related to resilience, suggesting that certain characteristics related to individuals' background contribute to their ability to bounce back from challenges.